2020
DOI: 10.1111/jgh.15190
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial intelligence using a convolutional neural network for diagnosis of early gastric cancer based on magnifying endoscopy with narrow‐band imaging

Abstract: gathered ME-NBI images and patients' clinical information. Kato Y provided valuable advice regarding the technical information and managed the AI-assisted CNN-CAD system and analyzed the data in this manuscript. All authors gave final approval for publication. Ueyama H, Nagahara A, and Tada T take full responsibility for the work as a whole, including the study design, access to data, and the decision to submit and publish the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 33 publications
0
62
0
1
Order By: Relevance
“…In other studies, a microendoscope with narrow-band imaging (ME-NBI) and EC were used in the classification of ESCC [180,181]. FICE and ME-NBI were used in the diagnosis of GC [182,183]. BLI and LCI were employed in the prediction of H. pylori infections.…”
Section: Applicationmentioning
confidence: 99%
“…In other studies, a microendoscope with narrow-band imaging (ME-NBI) and EC were used in the classification of ESCC [180,181]. FICE and ME-NBI were used in the diagnosis of GC [182,183]. BLI and LCI were employed in the prediction of H. pylori infections.…”
Section: Applicationmentioning
confidence: 99%
“…The integration of NBI and ANN has made amazing progress in early screening. Three studies respectively reported their models for the diagnosis of early GC[ 81 , 86 , 87 ]. For instance, Horiuchi et al [ 87 ] trained a CNN system that could differentiate between early GC and gastritis.…”
Section: Achievements Of Ann Research In Gi Diseasesmentioning
confidence: 99%
“…An array of CADx models has been developed to perform binary classification tasks for various qualitative properties of GI diseases, mostly for neoplastic lesions (Tables 3 4,10,22–34 and 4 16,35–41 ). The models determine and predict the group of qualitative property to which each lesion belongs.…”
Section: Cadxmentioning
confidence: 99%